1996
DOI: 10.1056/nejm199605023341803
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Antioxidant Vitamins and Death from Coronary Heart Disease in Postmenopausal Women

Abstract: These results suggest that in postmenopausal women the intake of vitamin E from food is inversely associated with the risk of death from coronary heart disease and that such women can lower their risk without using vitamin supplements. By contrast, the intake of vitamins A and C was not associated with lower risks of dying from coronary disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
258
2
14

Year Published

1998
1998
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 855 publications
(285 citation statements)
references
References 26 publications
5
258
2
14
Order By: Relevance
“…Antioxidants and heart disease in the Czech Republic M Boba Âk et al most observational studies which reported that persons with lower intakes or plasma levels of tocopherol or carotenoids are at increased risk of CVD (Rimm et al, 1993;Stampfer et al, 1993;Kardinaal et al, 1993;Riemersma, 1996;Riemersma et al, 1991;Street et al, 1994;Kushi et al, 1996). Several mechanisms have been proposed for the protective role of these vitamins, including their in-vitro and in-vivo antioxidant activity (Di Mascio et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidants and heart disease in the Czech Republic M Boba Âk et al most observational studies which reported that persons with lower intakes or plasma levels of tocopherol or carotenoids are at increased risk of CVD (Rimm et al, 1993;Stampfer et al, 1993;Kardinaal et al, 1993;Riemersma, 1996;Riemersma et al, 1991;Street et al, 1994;Kushi et al, 1996). Several mechanisms have been proposed for the protective role of these vitamins, including their in-vitro and in-vivo antioxidant activity (Di Mascio et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Four prospective studies conducted in the US have reported a beneficial effect of nut consumption on CHD incidence after follow-up ranging from six to 18 years of large cohorts of previously healthy subjects [1,41,42,43]. A pooled analysis of these studies shows that subjects in the highest intake group for nut consumption had a 37% reduction in multivariable-adjusted risk of fatal CHD [15].…”
Section: Epidemiological Studies Of Nut Consumption and Health Outmentioning
confidence: 99%
“…It must be underlined that in all these studies [1,41,42,43,44] the protective effect of nut consumption on total CHD or sudden cardiac death was independent of gender, age, body mass index, alcohol use, other nutritional characteristics or presence of cardiovascular risk factors. The dose-relationship between nut intake and incident CHD translates into an average 8.3 reduction for each weekly serving of nuts [15].…”
Section: Epidemiological Studies Of Nut Consumption and Health Outmentioning
confidence: 99%
“…The most notable positive findings on vitamin E come from two large epidemiological studies in the United States, where subjects with the highest vitamin E intake had a 30-40% reduction in CVD risk (Rimm et al, 1993;Stampfer et al, 1993). This association was mainly attributed to high vitamin E consumption from nutrient supplements; however, other observational studies have demonstrated protective effects from food-derived vitamin E alone (Knekt et al, 1994;Kushi et al, 1996). In contrast, most primary and secondary randomised clinical trials of vitamin E that have supplemented with doses well above upper dietary intake levels have not shown clear beneficial effects on CVD outcomes (Collaborative Group of the Primary Prevention Project, 2001;Czernichow & Hercberg, 2001;Hooper et al, 2001).…”
Section: Introductionmentioning
confidence: 99%